Analisis Historis Dan Fungsional Otoritas Moneter, OJK, Dan LPS Di Sistem Keuangan Indonesia - Nurliana Sianturi; Japar Arofik; Khofifah Kayla Syibillah; Eva Agustina Permadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Three main pillars play an important role in Indonesia's financial system, consisting of Bank Indonesia (BI) as the monetary authority, the Financial Services Authority (OJK) as the supervisor of the financial services industry, and the Deposit Insurance Corporation (LPS) as the deposit insurer and resolution of troubled banks. The purpose of this research is to study the historical and functional roles of these three institutions in maintaining the stability of the national financial system. The research found that synergy between BI, OJK, and LPS is essential to face domestic and international economic challenges, using a qualitative-descriptive literature study approach. Through interest rate policy and liquidity management, BI maintains monetary stability, OJK maintains financial sector integrity by overseeing emerging financial technologies, and LPS fosters public confidence in the banking sector through deposit insurance and bank disputes. Strengthening data-driven policies, improving public financial literacy, and stronger cross-sector collaboration are needed to address future challenges such as financial digitalization, economic globalization, and systemic risk. This study is expected to serve as a foundation for policy changes for a more resilient, inclusive, and sustainable Indonesian financial system.